Experiencing research-creation in urban studies. Lessons from an inquiry on the making of public space. (July 2018) - Vivant, Elsa
Abstract: This paper examines collaboration between artists and social scientists in urban studies. The author was a participant in experimental research commissioned by a new cultural institution, which examined how this institution might participate in the making of a public space. In this paper she analyses the methodologies of investigation and the discussions about forms and representations, and shows the difficulties and rewards of this type of collaboration. To what extent may research based on art and social sciences, and rooted in references to the methodologies and theories of both, be a relevant and alternative way to explore, investigate and represent an urban issue?